Indigenization of Political Identity in Postcolonial Hong Kong - Tang, Wenfang; Hung, Jennifer Sin Yu; Ho, Brian Ying Yeung (Frontiers in Political Science, 2022)
Drawing data collected in 2021 from a probability sample of Hong Kong residents, we examine their political identity with the former colonists and their post-colonial ruler in China. The data show an expected anti-China sentiment but an unexpectedly lukewarm attitude toward their former colonists. Instead, the survey respondents expressed strong feelings toward indigenization with traditional Chinese culture. For the sources of such sentiment, this paper finds that the anti-Mandarin language policy, the post-1997 anti-establishment education policy, and the anti-China media are particularly important reasons. This study attributes the trend of post-colonial indigenization to the political vacuum left by the departure of the old ruler and the new ruler's inability to indoctrinate the newly ruled under the postcolonial institutional design of One Country Two Systems. This trend of indigenization is likely to tilt toward identity with the Chinese state as China is stepping up its effort to make the territory more China-friendly.